Inhibition of multi-species biofilm formation using chitosan-based film supplemented with essential oils. (20th April 2023) - Mouhoub, Anouar; Er Raouan, Safae; Guendouz, Amine; El Alaoui-Talibi, Zainab; Ibnsouda Koraichi, Saad; El Abed, Soumya; Delattre, Cédric; El Modafar, Cherkaoui
Graphical abstract: Highlights: The elaboration of active packaging with antiadhesion activity using chitosan and essential oils. S. aureus, E. coli, E. hirae, and P. aeruginosa showed an absence of antagonism. The physicochemical properties of the chitosan-based film were modified by the incorporation of the essential oils. The CH-film containing the mixture of the essential oils exhibited the strongest antiadhesion activity. Abstract: The biofilm development following microbial attachment on food-grade surfaces represents a main problem in the food sector, leading to significant economic losses. To overcome that, the present investigation aimed to develop biodegradable films that protect against heterogeneous biofilms using chitosan and essential oils (EOs). First, the cross-streak method revealed the absence of antagonism between Staphylococcus aureus, Enterococcus hirae, Escherichia coli, and Pseudomonas aeruginosa strains. The contact angle findings revealed a drop in the electron acceptor (γ + ) and qualitative hydrophobicity ( θ w) associated with an increase in the Lifshitz-van Der Waals component (γ LW ) and electron donor (γ − ) regarding the treated chitosan-based films (CH-films). The environmental scanning electron microscopy (ESEM) images showed that among all the treatments, the CH-film treated with the Pelargonium asperum EO exhibited the weakest antiadhesion activity (73.89 ± 1.42% of the covered surface) while the CH-film treated with the Pelargonium asperum, Thymus satureioides, Cinnamomum zeylanicum, and Eugenia caryophyllus EOs mixture had the strongest activity (9.23 ± 1.66% of the covered surface). From these results, the CH-film containing the EOs mixture presents a high potential for utilization in the food industry as an active coating and packaging that prevent the microorganisms' attachment and the eventual biofilm development.